PENGARUH SUPERVISI KEPALA SEKOLAH DAN IKLIM KERJA TERHADAP KEPUASAN KERJA GURU SD NEGERI DI KECAMATAN NAN SABARIS KABUPATEN PADANG PARIAMAN - Amzah M; Susi Evanita (Program Studi Magister Manajemen, 2014)
The purpose of this study was to analyze: 1) The principal effect of supervision on the working climate at the elementary school in the Nan Sabaris District of Pariaman Region, 2) The principal effect of supervision on job satisfaction of teachers in public primary schools in the Nan Sabaris district of Pariaman Region, 3) The influence of climate on job satisfaction of teachers working in primary schools in the Nan Sabaris district of Padang Pariaman Region The research population is the whole entire elementary school teachers in Nan Sabaris District of Pariaman Region totaling 229 people. The sampling method is proportional random sampling. The number of samples is 70 teachers. Data analysis techniques using path analysis and hypotheses are tested with the F test and t test. The results of the study found that: 1) Supervising principals significantly influence the working climate in the District Elementary School District Nan Sabaris Padang Pariaman Region. If the principal can plan properly supervise, execute properly supervised, and can follow up properly supervised course will create a conducive working environment in schools. 2) Supervising principals significant effect on job satisfaction of primary school teachers in the District of Nan Sabaris Pariaman Region. The better implementation of the supervision by the principal must increase the job satisfaction of teachers in performing her daily duties at elementary school in the District of Nan Sabaris Pariaman Region. 3) Climate significant work on job satisfaction elementary school teacher in the district of Padang Pariaman Region Sabaris Nan. The better and more conducive working environment perceived by teachers in schools must improve the job satisfaction of teachers in performing her daily duties at the elementary school in the district of Padang Pariaman Region Nan Sabaris Key words: Principal Supervision, Work Climate, Work Satisfaction